Kenyatta and Britain An Account of Political Transformation, 1929-1963 - Maloba, W. O. (African Histories and Modernities, 2018)
This book is the first systematic political history of Jomo Kenyatta, Kenya's founding president. The first of two parts, it explores Kenyatta's formative years in nationalist activism in Kenya and Britain, the complex links between colonial and British intelligence services and Kenyatta's career and the political compromise he forged between Kenya and Britain. This book draws on primary sources to analyze this compromise, which marked his transformation from "leader to darkness and death" to the most beloved post-colonial African leader in the West. .